Choosing a Camera for 3D Mapping (Journal of Universal Science Research, 2023)
This paper examines the problem of three-dimensional mapping of space.. Creating 3D maps is an extremely urgent task. This is often done through mapping using a UAV. However, in order to create a technical map, it is necessary to select suitable sensors. This article provides an overview of sensors that can be used to create such maps. A pair of cameras has been selected, as well as a means of communication between them.